Search for the standard model Higgs boson in ZH→ + -bb̄ production with the D0 detector in 9.7fb -1 of pp̄ collisions at √s=1.96TeV - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Askew, A.; Atkins, S.; Augsten, K.; et al. (American Physical Society (APS), 2012)
We present a search for the standard model (SM) Higgs boson produced in association with a Z boson in 9.7fb -1 of pp̄ collisions collected with the D0 detector at the Fermilab Tevatron Collider at √s=1.96TeV. Selected events contain one reconstructed Z→e +e - or Z→μ +μ - candidate and at least two jets, including at least one jet identified as likely to contain a b quark. To validate the search procedure, we also measure the cross section for ZZ production in the same final state. It is found to be consistent with its SM prediction. We set upper limits on the ZH production cross section times branching ratio for H→bb̄ at the 95% C.L. for Higgs boson masses 90≤M H≤150GeV. The observed (expected) limit for M H=125GeV is 7.1 (5.1) times the SM cross section. © 2012 American Physical Society.
Keywords: Branching ratio; Cross section; Fermilab Tevatron collider; Final state; Higgs boson; Production cross section; Search procedures; The standard model; Upper limits; Z Bosons; High energy physics; Tellurium compounds; Bosons